Effect of curing conditions on the engineering properties of self-compacting concrete - Yazicioglu, S; Caliskan, S; Turk, K (Natl Inst Science Communication-Niscair, 2006)
The paper reports an experimental study investigating the influence of curing conditions on the engineering properties of self-compacting concretes (SCC). Portland cement (PC) concrete and two types of SCC. i.e.. SCC-1 with fly ash and SCC-II with silica fume, specimens are prepared and cured in three different curing conditions, namely standard 20 degrees C water, sealed and air cured for the periods of 3, 7, 14 and 28 days. At the end of each Curing period, compressive and tensile strength and ultrasonic pulse velocity (UPV) values are determined. The results showed that water cured specimens always give the highest values followed by those cured as sealed and in air irrespective of type and age of concrete and test methods. For both compressive and tensile strength tests, the SCC-II gives the highest values followed by SCC-I and then PC concrete for all curing periods and conditions. Whilst, the UPV results showed that the highest values are obtained from the SCC-I and then from the PC concrete and SCC-II for all curing conditions.